FROM THE PULPIT TO THE ALGORITHM: MILLENNIAL DIGITAL DA'WAH MANAGEMENT STRATEGY IN THE HIJRAH YOUTH SHIFT ECOSYSTEM AND WRITING PAUSE - Neneng Hasanah; Randi Tamirano; Sandi Maspika; Haikal Romadhan Al Yusad (J-MD Jurnal Manajemen Dakwah, 2026)
The transformation of the da'wah medium from a conventional pulpit to an algorithmic environment necessitates a new managerial framework. This study aims to analyze the digital da'wah management strategies within the ecosystems of Hijrah Youth Shift and Jeda Nulis. Employing a qualitative approach with a four-stage netnographic design (data entry, observation, interpretation, and validation), this study analyzed 200 top-performing content units across YouTube, Instagram, and TikTok from December 2025 to May 2026. The findings reconstruct the classical POAC management functions into the "Algorithmic Da'wah Management Model": Takhthith (data-driven algorithmic profiling), Tandzim (agile media team organization), Tawjih (hook-optimized actuating), and Riqabah (metric-based controlling). Empirical evidence indicates that algorithmic architecture acts as a primary gatekeeper of theological visibility. The analysis demonstrates that the highest interaction (85% engagement rate) correlates not with theological depth, but with the technical mastery of micro-duration content (30–60 seconds). Linking these findings to platformization and algorithmic governance theories, the study argues that digital religious actors globally must adopt identical managerial agility to survive the attention economy. This research contributes to digital religion studies by providing an empirically validated model for religious communication in a platformized society.